Initiation of self-care practices in heart failure patients: a phenomenological study - Suharsono, Tony; Ulya, Ikhda; Yona , Sri; Siswanto , Bambang Budi (Jurnal Ners, 2024)
Introduction: The incidence of heart failure continues to rise with advancing age, unabated by advancements in healthcare technology. Patients with heart failure are required to manage their care independently at home for the remainder of their lives. This study aimed to delve into the experiences of heart failure patients regarding self-care management at home. Methods: Nineteen patients with heart failure were chosen through purposive sampling and thorough interviews were conducted to collect their self-care treatment experiences. Content analysis was carried out to scrutinize the acquired data. Results: The analysis revealed four themes: patients' perception of heart failure diagnosis, efforts in self-care, readiness for self-care, and adoption of new healthy behaviors in heart failure. Eight categories were formulated within these themes, including "transitioning into a heart failure patient;” "recognizing the need for self-care;” "seeking information and heart failure therapy;” "facilitators and barriers in seeking information regarding self-care;” "social support and belief in engaging in self-care at home;” "self-confidence in engaging in self-care at home;” "efforts to develop self-care strategies;” and "engaging in new healthy behaviors as heart failure patients independently.” Conclusions: Patients become aware of the necessity for self-care upon experiencing discomfort due to symptoms resulting from their heart failure. Family support and the patient's belief system play pivotal roles in initiating self-care practices at home. Nurses should provide support to patients in fostering self-care practices within their homes.